Galaktik Astronomi Çalıştayı Bildiriler Kitabı / Galactic Astronomy Workshop Proceedings Book - Ak, Serap; Bilir, Selcuk (Istanbul University Press, 2021)
Surrounding all along the sky during nighttime and known as the "Milky Way" with its name coming from the mythology, the hazy structure is a part of our Galaxy that contains billions of stars. The Milky Way Galaxy, which we are the inhabitants of, is a system that contains much more than this hazy structure. Since the Milky Way's first observation with a telescope by Galileo in 1610, we are still trying to understand the structure, formation and evolution of our Galaxy, with the help of earth and space-based telescopes. In the study of the Milky Way as a galaxy, both extragalactic astronomy and stellar populations are utilized by using photometric, astrometric and spectral methods. Until the 21st century, traditional star counting analysis was used to understand the stellar populations and the basic structure of our Galaxy. Since the 21st century, with high resolution, sensitive, large scale and systematic CCD based sky surveys have come into play. Sent to space in 2013, the satellite Gaia has become one of the corner stones of Galactic astronomy and started the golden age of astrometry. With this satellite, it is aimed to observe over a billion of objects in our Galaxy. Thus, in the 21st century, the observational data accumulation, diversified with unprecedentedly sensitive astrometric, spectral and photometric data, and reached large dimensions, has given the opportunity to examine our Galaxy not only structurally but also in terms of its formation and evolution, and opened new horizons for the testing of chemo-dynamic evolutionary scenarios. Researches also focused on various topics of astronomy has been accomplished in Turkey for decades. As these studies are presented in international publications, they also found places in national congresses and workshops. Still, studies contributing to Galactic astronomy are carried out by examining sky survey data, star clusters, binary stars and similar objects, and observational initiatives and calibration projects to support these studies are carried out simultaneously. Moreover, these studies show remarkable developments in qualitative and quantitative terms. The aim of the meeting that took place on September 12-13 2019, titled "Galactic Astronomy Workshop" with international participants was to discuss the researches contributing directly or indirectly to Galactic astronomy starting from the observations of different objects, meeting the researchers to discuss this specific issue, establishing collaborations that can lead to joint studies and to foresee of these said studies in our country.